Beginning android 4 application development - Lee, Wei-Meng (Indianapolis, Indiana : John Wiley & Sons, 2012)
Understand Android OS for both smartphone and tablet programming This fast-paced introduction to the newest release of Android OS gives aspiring mobile app developers what they need to know to program for today?s hottest Android smartphones and tablets. Android 4 OS is, for the first time, a single solution for both smartphones and tablets, so if you master the information in this helpful guide, you?ll be well on your way to successful development for both devices. From using activities and intents and creating rich user interfaces to working with SMS, messaging APIs, and the Android SDK, what you need is here. Provides clear instructions backed by real-world programming examples Begins with the basics and covers everything Android 4 developers need to know for both smartphones and tablets Explains how to customize activities and intents, create rich user interfaces, and manage data Helps you work with SMS and messaging APIs, the Android SDK, and using location-based services Details how to package and publish your applications to the Android Market Beginning Android 4 Application Development pares down the most essential steps you need to know so you can start creating Android applications today
1. Getting started with Android programming -- 2. Activities, fragments, and intents -- 3. Getting to know the Android user interface -- 4. Designing your user interface with views -- 5. Displaying pictures and menus with views -- 6. Data persistence -- 7. Content providers -- 8. Messaging -- 9. Location-based services -- 10. Networking -- 11. Developing Android services -- 12. Publishing Android applications
Includes index
Keywords: Application software -- Development; Mobile computing